Plinio, N. H., 3, 28: Asturica, urbe magnifica (Estudios humanísticos. Geografía, historia y arte, 1994)
The purpose of this papen is to explain the meaning of the references to the urban sites of Hispania into Pliny the Elder's work, and, specifically, in the part where the city of Asturica Augusta is called urbs magnifica. As an introduction to the subject a shallow reference to the evolution of the town planning and development in Hispania between Augustus and the Flavii and the city of Asturica is made.